Pharmacophore mapping, 3D QSAR, docking, and ADME prediction studies of novel Benzothiazinone derivatives - Jahaan Shaikh; Afzal Nagani; Salman Patel; Harnisha Patel (International Journal of Antibiotics, 2024)
 Background Tuberculosis is a major public health concern worldwide which is caused by Mycobacterium tuberculosis. DprE1 (Decaprenyl Phosphoryl Ribose 2’- Epimerase) is the most challenging target for development of novel anti- tubercular agents because it is a small protein and located into cytoplasmic membrane. So, novel anti-TB drugs did not bound effectively with it. DprE1 catalyzes the oxidation of the 2’ hydroxyl group of DPR (Decaprenyl Phosphoryl D- Ribose) to give Ketoribose DPX (Decaprenyl Phosphoryl 2-Ketoribose). Benzothiazinone is the most potent Pharmacophore as DprE1 inhibitors. BTZ043, BTZ038, PBTZ169 and TMC-207 (Bedaquiline) are clinical trial drugs as DprE1 inhibitors.  Objective To develop novel Benzothiazinone derivatives by performing Pharmacophore mapping, 3D QSAR, docking and ADME prediction studies.  Method Pharmacophore mapping of Pyrazolopyridine, Dinitrobenzamide, and Benzothiazinone derivatives gives information about essential features required for producing a biological response. Benzothiazinone (Ligand code: 73) has the essential features with the Fitness score for active ligands- 3.000 and as a Reference Ligand. (Pharmacophore Hypothesis: AHHRR_1). It is validated by ROC (Receiver Operating Characteristics) value as 0.71 which indicates perfect performance of Pharmacophore mapping. Benzothiazinone congeneric series are required for building 3D QSAR model. The validation criteria of 3D QSAR Model- Standard Deviation is 0.1531, R 2 value is 0.9754, R 2 CV (Cross Validation) value is 0.2118, R 2 Scramble value is 0.9500, Stability value is 0.261, F value (Variance) is 205.0 (For Training set), P value (Probability value) is 1.58e-23, Q 2 value is 0.7632 and Pearson-r value is 0.8939 (For Test set). PBTZ129 is the Reference Molecule (MIC value- 0.00019 µM). The contour maps indicate the positions at which steric, electrostatic, hydrophobic, H-bond acceptor and H-bond donor groups are required for generating SAR.  Result Novel Benzothiazinone derivatives designed according to contour maps and their biological activities were predicted. Docking scores (PDB ID- 4NCR) are good and amino acid interactions of novel Benzothiazinone derivatives are matched with in-built ligand 26J. Docking validation was also performed by comparing RMSD values of superimposed atoms of co-crystal ligand and its conformer.  Conclusion These novel molecules can be proposed for synthesis and biological evaluation.
Keywords: 3D QSAR; ADME prediction; Benzothiazinone; Docking; DprE1; Pharmacophore mapping